Current Status of Ceramic Industry and VR Technology Used in Ceramic Display and Dissemination - Xue Li (Hindawi Limited, 2021)
With the deepening of reform and opening up, the development of China’s ceramic industry has been rapidly improved, leading the world, and various ceramic varieties have also been greatly developed. However, as the growth rate of the global economy has gradually slowed down and structural imbalances have become more obvious, China’s economy has gradually entered a new development trend. In the context of supply-side structural reforms, the severe macroenvironment and policy pressure to eliminate backward production capacity have further promoted the development of China’s ceramic industry to face greater challenges. In the context of the rapid development of various high-tech technologies such as “Internet +” and intelligent manufacturing, this paper discusses the use of VR technology in the design of ceramics from the principles and characteristics of ceramic design and, according to the characteristics of virtual design of ceramics, demonstrates the feasibility of its shape, decoration, color matching, and so on. The ceramics are classified according to their use functions, and the characteristics of different types of virtual display of ceramics and their suitable virtual display methods are discussed. Finally, this paper combines panoramic image display technology and graphic VR display technology to create the best virtual display method suitable for different types of ceramic products, implements the interactive design in virtual software, and then performs virtual display.